Influence of El Niño-Southern Oscillation on baroclinic instability and storm tracks in the Southern Hemisphere - Machado, Jeferson Prietsch [UNESP]; Justino, Flávio; Souza, Caio Demétrio [UNESP] (Wiley, 2020)
Earth's weather and climate are strongly influenced by synoptic scale systems such as extratropical cyclones. From this point of view, investigating the mechanisms associated with cyclogenesis, such as baroclinic instability (BI), which are defined by the thermal gradient and wind shear, are extremely important. However, atmospheric teleconnection patterns such as the El Niño-Southern Oscillation (ENSO) phenomenon may affect BI in the preferred region of extratropical cyclones, known as the storm track (ST) region. Therefore, the present study shows the impact of ENSO on BI and STs in the Southern Hemisphere. BI is determined by means of the Eady growth rate method, while the STs are calculated from the kinetic energy and by means of the meridional heat transport. In general, the results show that STs calculated from the BI and the kinetic energy show seasonal variability during ENSO events. This results in Southern Hemisphere extratropical cyclones being more intense with trajectories towards lower (higher) latitudes during El Niño (La Niña) summers. In contrast, little difference is seen in El Niño and La Niña winters. For the calculation of the meridional heat transport at 500 hPa, the Climate Forecast System Reanalysis produced weaker transport relative to ERA-Interim and previous studies.
Keywords: baroclinic activity; climatology; ENSO